2015
DOI: 10.1126/science.aaa5329
|View full text |Cite
|
Sign up to set email alerts
|

Subatomic resolution force microscopy reveals internal structure and adsorption sites of small iron clusters

Abstract: Metal clusters really close-up Atomic force microscopy (AFM) can be used to reveal subatomic structures. By this means, Emmrich et al. found that individual copper and iron atoms formed toroidal structures on a copper surface. These shapes arise from the electrostatic attractions in the center of the atoms and Pauli repulsions at their edges. Individual atoms within clusters have underlying surface symmetry and can bind to different surface sites as clusters form.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
97
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 46 publications
13
97
1
2
Order By: Relevance
“…The hcp site configuration has a slightly higher energy (by 10 meV) while the bridge and top sites are 0.28 and 0.78 eV higher in energy than the fcc adsorption site, respectively. Preferential adsorption on the fcc site is not surprising, as it has been already reported for this system [8,30]. A similarly small difference of 6 meV in favor of fcc with respect to hcp sites has been reported also for Cu adatoms on Cu(111) [31].…”
Section: A Fe Monomers On Cu(111)supporting
confidence: 51%
“…The hcp site configuration has a slightly higher energy (by 10 meV) while the bridge and top sites are 0.28 and 0.78 eV higher in energy than the fcc adsorption site, respectively. Preferential adsorption on the fcc site is not surprising, as it has been already reported for this system [8,30]. A similarly small difference of 6 meV in favor of fcc with respect to hcp sites has been reported also for Cu adatoms on Cu(111) [31].…”
Section: A Fe Monomers On Cu(111)supporting
confidence: 51%
“…Noncontact mode exerts the least lateral or normal forces on the sample and is very useful for measurements requiring the highest sensitivity and delicacy. 13,22,32,33 Key AFM hardware elements…”
Section: Non-contact Modementioning
confidence: 99%
“…The metallic tip apex atom has a dipole moment induced by the Smoluchowski effect [25], whose direction is the same as that of the CO molecule adsorbed on the surface [26]. Thus in the distance regime where the electrostatic interaction between the tip and the molecule dominates, the force between them is attractive.* okabayashi@staff.kanazawa-u.ac.jp When the tip is scanned over the CO molecule, this attractive force appears as a dip (smaller value) in the frequency-shift image for each atom at its apex, i.e., the number of the attractive force minima provides the number of atoms composing the tip apex [27].In this paper, we have investigated the tip-structuredependent IETS for individual CO molecules on a Cu surface by combining STM and AFM. We have found that a tip with a single atom on its apex (single-atom tip) gives a stronger IET signal compared with a blunt tip consisting of four atoms on the apex (four-atom tip) for a CO molecule on a Cu(111) surface.…”
mentioning
confidence: 99%
“…* okabayashi@staff.kanazawa-u.ac.jp When the tip is scanned over the CO molecule, this attractive force appears as a dip (smaller value) in the frequency-shift image for each atom at its apex, i.e., the number of the attractive force minima provides the number of atoms composing the tip apex [27].…”
mentioning
confidence: 99%